Strategi Komunikasi Pemasaran Milenial Studio Melalui Media Sosial TikTok - Soraya, Nabilla Dwi; Ramdhani, Muhammad; Oxygentri, Oky (CV. ITTC INDONESIA, 2024)
As time goes by, TikTok social media now occupies the top rank in the category of most social media usage time. TikTok is widely used by people today because it is easy to access. That's why almost every group has social media. TikTok's reach is very wide so that the information and content created spreads more easily and quickly. Therefore, TikTok social media information technology is widely used by business or company users to promote their products and services. One of the companies in the field of photo and video services is the Milenial Studio photo studio. This research aims to determine the marketing communication strategy for the Milenial Studio photo studio via TikTok social media. The subject of this research was a photo studio located in Karawang and consisted of 4 informants. The data collection techniques used were in-depth interviews, observation, documentation and literature study.The research results show that the marketing communication strategy is very effective and important for the Milenial Studio photo studio to promote and sell its photo and video services. Some of the strategies that have been identified include the marketing mix and what the owner of Milenial Studio himself said was that they also collaborate with schools by providing photo and video services for school yearbooks.